The shifting space of ontology: appeals to crisis and the reformulation of nation, race, and biology in educational reform. Issue 2 (4th March 2018) - Kung, Sunhye
ABSTRACT: This article considers a conflated ontological space where national projections named Koreanness are conjoined through national educational reform discourses associated with excellence and equality . It focuses on the shifting educational reform narratives that made appeals to notions of crisis before and after the IMF (International Monetary Fund) occurrence of 1997 in South Korea. Using Foucault's concept of biopower and Lyotard's concept of performativity, two representative Korean language newspapers (1995–1997 and 2005–2007) are analysed. The article concludes that the appeal to a sense of crisis through references to globalization (1995–1997) and the IMF (2005–2007) was utilized to elaborate the ontological shift in Koreanness-as-race from blood-tie (biology-as-nation-race) to label-based codification (biology-as-biopolitical species). The shifting nature of Koreanness elaborated here may ultimately offer suggestions for scenarios beyond its geopolitical realm, provoking reconsideration of convenient binaries, economic reductionism, and the frequent naturalization of biological rationalities in educational research.